Contemporary landscape architecture. (Köln : DAAB, 2008)
The landscape architect shapes the terrain and the space around a pre-existing construction or a developing urban or regional project. His aim is to offer the most poetic transcription of the language associated with a given architectural calculation. These professionals work with animated and inanimate physical structures which spring from geographical and social contexts, as well as from technical and economical conditions. Their imagination is the motor behind the creative, competent and playful solutions. The fifty projects presented in this book primarily show the designs of new spaces and successful restoration of others, which had previously had completely different uses, like a quarry or an industrial center. An index with contact information on the respective architects and designers is enclosed.
Bevat teksten in het Engels, Frans, Duits, Spaans en Italiaans.
Keywords: Landschapsarchitectuur